Analisis Pengelolaan Keuangan Pada Kantor Dinas Perhubungan Kutacane (Dishub) Kutacane - Sophia Kharisah (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2024)
This study aims to determine how the financial management at the Kutacane Transportation Department office. Financial Management in question is Financial Management in accordance with public accounting standards. Data analysis was carried out using descriptive analysis techniques. The results of this study indicate that Financial Management has been assessed by the North Sumatra Provincial Transportation Office very much. Based on the percentage obtained from the calculation of the explanation above, 96.3% of the answers stated "Yes". While 3.7% of the interview answers stated "No", the authors concluded that the Financial Management at the North Sumatra Provincial Transportation Service Office (Dishub) Kutacane was very good.